Determinants of profitability of post merger and acquisition companies: evidence of companies in Malaysia / Hayat Jamaludin and Muhammad Naufal Ahmad Barizi - Jamaludin, Hayat; Ahmad Barizi, Muhammad Naufal (2014)
The main objective of this research is to investigate determinants of profitability of post merger and acquisition companies in Malaysia that made announcement in Bursa Malaysia. The scope of this study covers 4 years included with the announcement year of acquisition companies. The data is derived from Bloomberg which consist of 37 companies. Moreover, the data has been collected from various sectors such as consumer industrial, financial, basic material, technology, and communication. This study employs the profitability as dependent variable while the independent variables are liquidity ratio, activity ratio, and leverage ratio. Based on the empirical result show that liquidity ratio and leverage ratio is significantly related to profitability. However, the study finds activity ratio insignificant toward profitability